Pengaruh Gaya Kepemimpinan Situasional Dan Motivasi Kerja Terhadap Komitmen Dan Prestasi Kerja Karyawan Rumah Sakit Anak Dan Bersalin Muhammadiyah Tuban - Budi Widianto, Agung (Program Doktor Ilmu Ekonomi, 2013)
Hospitals as one form of business services for the community-oriented services in the field of health care is not much different form other endeavors. Understanding of the hospital is an institution of health care professionals whose services are provided by doctors, nurses and other health experts. Rumah Sakit Anak dan Bersalin Muhammadiyah Tuban located at Jalan Diponegoro No. 1 Tuban with type